2013
DOI: 10.1371/journal.pone.0075653
|View full text |Cite
|
Sign up to set email alerts
|

Diatom Proteomics Reveals Unique Acclimation Strategies to Mitigate Fe Limitation

Abstract: Phytoplankton growth rates are limited by the supply of iron (Fe) in approximately one third of the open ocean, with major implications for carbon dioxide sequestration and carbon (C) biogeochemistry. To date, understanding how alteration of Fe supply changes phytoplankton physiology has focused on traditional metrics such as growth rate, elemental composition, and biophysical measurements such as photosynthetic competence (Fv/Fm). Researchers have subsequently employed transcriptomics to probe relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
115
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 83 publications
(117 reference statements)
14
115
2
Order By: Relevance
“…This supports that diatoms may be capable of shuffling energy pools into either the CCM or RubisCO production depending on Fe bioavailability. Interestingly, in laboratory-based proteomic analyses with cultures of the coastal diatom T. pseudonana, RubisCO was similarly more highly expressed under Fe limitation, while PEPC protein levels were higher under Fe-replete conditions (Nunn et al, 2013). Consistent with our hypothesis, Hopkinson et al (2010) attributed increases in biomass following CO 2 -enrichment of an Fe-limited phytoplankton community in the HNLC Northeast Pacific Ocean to downregulation of the CCM in order to conserve iron and photosynthetically-produced energy.…”
Section: Carbon-related Gene Expression Responses As a Function Of Fesupporting
confidence: 74%
“…This supports that diatoms may be capable of shuffling energy pools into either the CCM or RubisCO production depending on Fe bioavailability. Interestingly, in laboratory-based proteomic analyses with cultures of the coastal diatom T. pseudonana, RubisCO was similarly more highly expressed under Fe limitation, while PEPC protein levels were higher under Fe-replete conditions (Nunn et al, 2013). Consistent with our hypothesis, Hopkinson et al (2010) attributed increases in biomass following CO 2 -enrichment of an Fe-limited phytoplankton community in the HNLC Northeast Pacific Ocean to downregulation of the CCM in order to conserve iron and photosynthetically-produced energy.…”
Section: Carbon-related Gene Expression Responses As a Function Of Fesupporting
confidence: 74%
“…Carbohydrate exudation products tend to be linked to nutrient limitation and the stationary growth phase of cells (e.g., Myklestad, 1977;Liu et al, 2001), such as at the decline of a phytoplankton bloom when cells continue to fix carbon photosynthetically but have insufficient nutrients available for macromolecular synthesis (e.g., Boyd et al, 2005). To date, a clear link between phytoplankton Fe limitation and the specific production of exopolymeric substances is missing but putative proteomic evidence has been presented (Nunn et al, 2013). However, EPS release is not be restricted to surface waters; bacterial exopolymers were reported in the deep-ocean, including hydrothermal vents (e.g., Nichols et al, 2005), but their specific role(s) within Fe biogeochemistry remains unknown.…”
Section: Exopolymeric Substances and Saccharidesmentioning
confidence: 99%
“…Earlier studies have shown that the uptake rates per unit of cell surface are similar among species with different iron requirements and as a consequence smaller cells with higher surface-to-volume ratios are favored under iron limitation (10,11). Acclimation to low iron induces rapid changes in the Photosystem (PS) II-to-PSI ratio and a global remodeling of the photosynthetic machinery (12), the down-regulation of nitrogen-reducing enzymes such as Fe-dependent nitrate and nitrite reductases, and the upregulation of enzymes involved in nitrogen recycling (13). In oceanic diatoms, metabolic adaptation to iron limitation involves a decrease of PSI and cytochrome b6/f requirements (14) and the utilization of copper-dependent plastocyanin instead of cytochrome c 6 (15,16).…”
mentioning
confidence: 99%